La Morphological awareness for the development of the lexical competence of the English language - Díaz, Carlos (2023)
This study centers on second language English learners and their limited vocabulary proficiency. Morphological awareness is acknowledged as crucial for developing lexical competence. This review explores the implications of morphological awareness (structure, analysis, and decoding) on lexical competence (vocabulary breadth, depth, and organization). The methodology employed is socio-educational, bibliographic, descriptive, and documentary. The transfer technique facilitated gathering and analyzing relevant bibliographic records. Databases such as ERIC, Scopus, Wiley Online Library, ABELL, Google Scholar, university repositories, and international journals were utilized, in turn, manual filters and keywords enhanced information gathering. Findings demonstrate that morphological awareness significantly enhances lexical proficiency in English across all dimensions. Grasping inflectional, derivational, and compounded forms enhances vocabulary breadth, depth, and organization. This awareness aids word recognition, comprehension, relationships, nuances, and meanings. Appreciating morphological patterns assists in word classification and arrangement and its pivotal role in increasing lexical proficiency benefits vocabulary organization, depth, and breadth. Educators can implement effective teaching techniques, emphasizing inflection, derivation, and lexical compounding, to enhance students' lexical competence and English proficiency, leveraging the scope of morphological awareness.